Effect of BN nanosheet concentration on space charge characteristics in XLPE/BNNS nanocomposites. (16th October 2019) - Li, Guochang; Zhou, Xuguang; Wei, Yanhui; Hao, Chuncheng; Lei, Qingquan
Abstract: Space charge accumulation in insulation material is one of the key factors that threaten the safe operation of high voltage direct current (HVDC) cable. Nanocomposites have been considered as the potential material to solve the problem of charge accumulation in HVDC cable. In the work, the effect of boron nitride nanosheets (BNNSs) concentration on space charge accumulation characteristics in XLPE/BNNS nanocomposite have been explored. The experimental results indicate that space charge in nanocomposite can be effectively suppressed when a small amount of BN nanosheet (<0.5 wt%) is doped into the matrix. It is mainly due to the introduction of deep traps at the interface between electrode and nanocomposite, and the 'charge barrier effect' has been formed to inhibit charge injection. The trap level of nanocomposite is 0.95 eV and the trap number is 2.43 × 10 20 m −3 for the concentration of 0.1 wt%. While, the charge inhibition effect in the nanocomposite becomes weaken with the increase of the BNNS concentration. PEA experimental results show that the accumulated charges increase when the concentration is 1 wt%, the charge amount in the composite reaches 1.08 × 10 −5 C, and the local electric field distortion rate is 9.5%. For high concentration (>2 wt%∼3 wt%), the calculated results indicate that more relatively shallow traps are introduced in the composite, resulting in few accumulated charges. The trap level is 0.62 eV and the trapped charge density is 5.76 × 10 20 m −3 at 5 wt%, which will enhance the charge hopping probability between the adjacent trap centers.